Reproductive traits and lactation performance of Kenana cows at Umbenein Livestock Research Station, Sinnar State, Sudan - A. Mudawi, Tilal M.; A. Ahmed, Rashid A. (Gezira Journal of Agricultural Science; Vol 17 No 2 (2019), 2021)
Sudanese Kenana breed is one of the largest east African Zebu cattle. Its performance is close to the best dairy breeds in Africa. This study aimed to estimate selected reproduction and lactation traits and effects of sire, lactation number and year of calving on those traits in Kenana cows at Umbenein Livestock Research Station, Sinnar State, Sudan. The official records of the station during the years 2000 -2017 were used. Overall mean of age at first calving, calving interval, open, dry and lactation periods (day) and lactation, daily and standard yields (kg) were 1673, 468, 184, 151, 315, 2260, 7 and 2042, respectively. The daughters of the sire of Umbenein Research Station showed earlier age at first calving and shorter calving interval, open and dry periods, while those of the sire of Umbenein village were higher in lactation, daily and standard yields. Lactation number had significant effects (P≤0.05) on lactation yield, calving interval and open period and were least in the fourth lactation. Daily and standard yields were higher in the third lactation, with a clear drop in the fourth one. Year of calving had significant effects (P≤0.05) on calving interval, open period, daily and standard yields. All traits studied, except lactation period, were higher in 2009-2011 years of calving and decreased in 2012-2014 and 2015-2017 calvings.